An Investigation of Attached Biomass on Bio-Media using Scanning Electron Microscopy - Hayder, Gasim; Perumulselum, Puniyarasen (International Journal of Engineering and Technology, 2018)
Biological film that attached to bio-media in attached growth wastewater treatment processes needs to be monitored and evaluated as it reflects the performance of the plant. Using Scanning Electron Microscopy (SEM) is an effective way for the examination of biofilms. Three different types of bio-media (bio-balls) were used to study the biofilm thickness using SEM. They are fin ball, spike ball and cage ball. Each type of bio-balls was cut into pieces since the size of SEM sample must be less than 25 mm. The fin ball was cut into three pieces, the spike ball was cut into two pieces and the cage ball was cut into one piece. Only the non-identical parts from the bio-balls were chosen for SEM test. The cut pieces with biofilm growth were overnight dehydrated in laboratory oven before bring to the SEM for measuring and analysis of the thickness of biofilm growth. Based on average biofilm thickness of the cut pieces extracted from SEM test, cage ball and fin ball recorded the highest biofilm while spike ball has the lowest biofilm growth on it.